Rancang Bangun Alat Ukur Kualitas Air pada Penampungan Air Hujan dengan Sensor TDS Berbasis Mikrokontroller ESP8266 - Isvine Zahroya Jasmine Marzuki Fahd; Mohammad Farras Hasan; Aisyah Fadilah Andoko; Andrijani Sumarahinsih (Universitas Merdeka Malang, 2023)
Water quality that is not good can be a disease. Especially diseases related to digestion. Cause of poor water quality can be seen from where the water is obtained. Therefore, this research is expected to help the community to overcome this. Water quality measuring instrument with the implementation of a Total Dissolve Solid (TDS) sensor based on the ESP8266. Purposed research uses Internet of Things (IoT) media to read TDS values and uses Blynk app as a remote control of the device. This study used 3 water samples as a comparison of TDS values, rainwater, ready-to-drink water, and PDAM tap water.